Overcoming five key challenges to make the energy transition a just labor transition - Luis Fernández Intriago; Sharan Burrow; Shouvik Chakraborty; Reza Daniels; Alan Finkelstein Shapiro; Helena Garcia; Raphael Heffron; Michael Jakob; Markus Janser; Suzi Kerr; Catherine Leining; Dave Maré; et al. (Nature Communications)
Shifting rapidly to a low-emissions global economy could severely disrupt workers’ livelihoods and their communities, exacerbating inequalities and perpetuating injustice. In a Just Labor Transition, strategic policies prepare workers for new jobs, enable inclusive decision-making with meaningful participation of workers and their representatives (including labor unions and other collective organizations), and secure social license for change.